A Structured Medical Interviewing Course: Seven Standardized Patient Cases - Kayleen Papin; Joan Bedinghaus (Association of American Medical Colleges, 2008)
Abstract Introduction Standardized patient (SP) cases allow first-year medical students to practice core interviewing skills in a safe experiential group environment. Through SP cases, students practice establishing rapport, collecting the history for each case, and attending to patient-centered concerns. The M-1 Interviewing Course at the Medical College of Wisconsin uses six SP cases. This resource contains a complete guide for the six cases that are currently being used in the course: acute back pain, first prenatal visit, normal breastfed newborn, depression in an older adult, an unwanted pregnancy, and routine physical for a 60-year-old man. An additional seventh case that was used in the past consisting of a routine physical for a woman in her forties is also included. Methods Groups of six students meet with one facilitator and a series of SPs. Each week, two students are assigned to interview the SP. By the end of the course, each student has participated in two interviews, observed and discussed four additional interviews, and completed six chart-style notes. As each of the cases progress, students practice additional skills such as: collecting family and genetic history, collecting birth and newborn history, collecting sexual and menstrual history, smoking cessation counseling, depression and suicide assessment, and collecting diet and exercise history. Results On self-assessment surveys, students say they have made significant improvements in interviewing skills. Discussion The effectiveness of this tool is heavily dependent on the quality and training of the SPs and faculty facilitators, and the use of trained SPs is strongly recommended. The students perform more efficiently if the goals of the interviewing assignment and strategies for meeting them are discussed before the interviews.